Konflik dalam Kepemimpinan (Studi Literatur) - Mudarti, Hasni; Fatrisna, Yuli; Zahara, Sri; SD Negeri 6 Sijunjung, SD Negeri 6 Sijunjung; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to analyze the factors causing conflicts in leadership and the techniques for resolving them. This research uses a qualitative approach with the literature review method. Literature searches were conducted through several digital databases, namely Google Scholar. The keywords used in the literature search process include: leadership conflict, organizational conflict, leadership style and conflict, conflict management, leadership and conflict, as well as conflict resolution in organizations. The data analysis technique employs content analysis with a thematic approach. The results of the analysis show that conflict in leadership is an unavoidable phenomenon in every organization, whether in the public or private sector. Conflicts often arise from differences in opinions, goals, and interests among individuals or groups (organizations) involved. In this context, leaders play a crucial role in managing and resolving the conflicts that occur, thus promoting the effective achievement of organizational goals. Conflicts can have positive and negative impacts, depending on how they are managed. Conflicts that are resolved fairly and peacefully can lead to strong harmony and togetherness. Based on this, it can be concluded that conflicts become negative if not managed well, and conversely, conflicts can be positive if managed well and systematically